DEVELOPING THE SKILL OF ANALYZING GENETIC RELATIONSHIPS IN LITERATURE AND PAINTING AMONG PHILOLOGY STUDENTS BY MEANS OF A PROBLEM LECTURE: BASED ON THE FORMATION AND DEVELOPMENT OF THE CANON OF THE IMAGE OF A BEAUTIFUL LADY (PART 2. THE MIDDLE AGE (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-3-128-141This article is a continuation of the previously published first part. The first article described the work on developing philology students' skills in analyzing genetic relationships in literature and painting using the example of the formation and development of the canon of the image of a Beautiful Lady in the era of Antiquity. This article reveals the didactic potential of a problematic lecture in the course of studying the canon of the image of a Beautiful Lady in the Middle Ages and the Renaissance. The main questions of the thematic blocks are presented, their summary is disclosed, methodological explanations are given, examples of problematic tasks, questions and approximate answers to them are given. The materials proposed in the article can be used in the practice of teachers of literature and art, introducing the experience of an intermediate approach to understanding artistic phenomena.Key words: intermediate analysis, genetic connections, problem lecture, the canon, DNA images, the image of a Beautiful Lady